FORMATION OF THE MARKET SITUATION OF MAIZE IN THE KIEV REGION (INNOVATIVE ECONOMY, 2020)
Vashchenko I.V. FORMATION OF THE MARKET SITUATION OF MAIZE IN THE KIEV REGIONPurpose. The aim of the article is to assess the state of formation of the market situation for maize in the Kiev region.Methodology of research. The following methods are used in conducting the research: monographic (for the comprehensive and in-depth study of individual phenomena, processes and the identification of causal relationships of their development), systemic (consists in researching certain objects as complex systems), economics and mathematics (enabled to establish the quantitative effect of individual factors on the result of the study), statistical (when working with statistical information and outputting analytical expressions).Findings. It has been established that the corn market in Ukraine in recent years has become more and more developed and more profitable, there is an increase in the volume of its total production.It is revealed that in recent years, the growth of demand for it on the world market has been an impetus for national producers of this product in our country. An indication of this is the growth of the cultivated area under cultivation almost twice during the ten-year period, as well as the corresponding increase in its exports outside the country.It is determined that Ukraine, developing all resource possibilities for corn growing, will become the leading supplier of maize on the world market, and, using all available potential, will contribute to the growth of market efficiency, which will lead to rapid economic growth in the agro-industrial complex and the economy as a whole.Originality. Theoretical and practical recommendations for formation of the market conditions of maize in the Kyiv region are substantiated.Practical value. The results of our study, namely the study of the dependence of maize crop productivity on factors of elemental costs, can be used to solve the problems of forming the market situation for corn.Key words: maize; market; regression; analysis; conjuncture; enterprise; products.
Keywords: Key words; maize; market; regression; analysis; conjuncture; enterprise; products.